CONTRIBUTION OF THE BOTANIKAL GARDEN IN GREENING OF INTERDIAL ZONE OF LAKE YSSYK-KUL (SURVEY OF SCIENTIFIC WORKS) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The article provides informationon research conducted by the staff of theBotanical garden regarding greening of thetideline of lake Yssyk-Kul and a list of theirworks published from 1959 to 1996
Keywords: : Botanical garden, greening, of interdial zone, of lake Yssyk-Kul, of scientific works.